Applying quantile regression to determine the effects of household characteristics on household saving rates in Vietnam - Hua, Thanh Xuan (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to analyse the determinants of the saving behaviour of Vietnamese households and to explore the possible heterogeneity of household saving propensities. Design/methodology/approach The authors estimate the effects of household characteristics on Vietnamese household saving rates by means of a quantile regression approach using the Vietnam Household Living Standard Survey 2010 data set. Findings The results suggest that the way household characteristics influence saving rates is different for each quantile of the household saving rate distribution. Household characteristics tend to have stronger effects at lower quantiles. Particularly, the marginal propensity to save of households at low quantiles is higher than those at high quantiles. Analysing rural and urban households separately, the authors find evidence that household and household head characteristics have stronger significant effects for rural than for urban households. Children and elderly members should be treated as part of the household labour force, instead of household dependency, since both of them increase household saving rates. Originality/value This research contributes to the literature on Vietnamese household saving behaviours, especially for households living in urban areas.